Risk assessment of land-use suitability and application to Tangshan City. (27th September 2010) - Zhu, Qingjie; Su, Youpo; Wu, Desheng Dash
Risk assessment for suitability is one of the main problems in city landuse planning for disaster prevention. Decision-making strategy using GIS-based Ordered Weighted Averaging (OWA) method is discussed through analysing OWA evaluation procedure. Data of geological disaster in Tangshan City are used to calculate the distances from dangerous areas or safety area to yield evaluation criteria for all disaster factors of land-use suitability.